PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN GENDER PADA SIKAP ETIS MAHASISWA MAGISTER AKUNTANSI UNIVERSITAS UDAYANA - Wardana, A.A.Gd. Agung Wisnu; Mimba, Ni Putu Sri Harta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
This study aims to provide empirical evidence about the influence of intellectual intelligence, emotional intelligence, spiritual intelligence and gender on ethical attitudes accounting students of postgraduate program in Udayana University. The sampling method used is nonprobability sampling with total sample of 111 respondents and using multiple linear regression analysis. The results of this study prove that intellectual intelligence, emotional intelligence and spiritual intelligence have positive effect on the ethical attitudes of accounting students. This means that the higher the level of intellectual intelligence, emotional intelligence and spiritual intelligence of students, the higher ethical attidute will be. This study also confirm that gender has no effect on the ethical attitudes of accounting students.
Keywords: Intellectual intelligence, emotional intelligence, spiritual intelligence, gender, ethical attitude